Nb-induced ultra-fine grain Fe-based laser cladding layer with high abrasion and corrosion resistance and cladding process of Nb-induced ultra-fine grain Fe-based laser cladding layer

By adding an appropriate amount of Nb elements and specific alloy powder to the Fe-based laser cladding layer, the laser cladding process of synchronous powder feeding is solved, and the problems of high powder particle size requirements and complex process in the prior art are achieved, and high resistance is achieved The Fe-based laser cladding with corrosion and high microhardness significantly improves the simplicity and efficiency of the process.

CN119243143AInactive Publication Date: 2025-01-03QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)

Patent Information

Application Number
CN202411365973.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, when preparing a high corrosion-resistant submicro-nano crystal Fe-based laser cladding layer, the powder particle size requirements are high and the process is complex, making it difficult to achieve synchronous powder feeding, and the cooling speed of forced cooling is not easy to control, which affects the simplicity of the process. and efficiency.

Method used

Using the process of ultrafine crystallization Fe-based high-wear resistance laser cladding layer of Nb, the alloy powder consists of 60.6 wt.% reduced iron powder, 32.4 wt.% iron vanadium powder, 6.1 wt.% graphite powder and 0.9wt.% niobium powder is laser cladded by synchronous powder feeding. The parameters are laser power 1000W, cladding head distance 24mm, overlap rate 35%, pulse frequency 4500Hz, duty cycle 95%, cladding speed 12mm /s, pure argon is used as powder feeding gas and protective gas.

Benefits of technology

The submicron ultrafine grain size and high microhardness of the cladding layer are achieved, with a microhardness of 960HV0.2, and abrasion resistance of 7.3 times that of the 27SiMn substrate. The process is simple, no forced cooling is required, and the alloy powder particle size is moderate. Coaxial powder feeding can be used, which significantly improves the feasibility of the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243143A_ABST
    Figure CN119243143A_ABST
Patent Text Reader

Abstract

According to the cladding process of the Nb-induced ultra-fine grain Fe-based high-abrasion-resistant laser cladding layer, the cladding layer is prepared on a 27SiMn steel base material through a laser cladding method, and alloy powder used for cladding is composed of 60.6 wt.% of reduced iron powder, 0.6 wt.% of iron powder, 0.5 wt.% of iron powder, 0.5 wt.% of magnesium powder, 0.5 wt.% of magnesium powder, 0.5 wt.% of magnesium powder, 0.5 wt.% of magnesium powder, 0.5 wt.% of magnesium powder, 0.5 wt.% of magnesium powder, 0.5 wt.% of magnesium powder, 0.5 wt.% of magnesium powder, 0.5 wt.% of magnesium powder and 0.5 wt.% of magnesium powder. 32.4 wt.% of ferrovanadium powder, 6.1 wt.% of graphite powder and 0.9 wt.% of niobium powder. The average grain size of the cladding layer reaches the submicron ultra-fine grain size and is 0.96 mu m, the average microhardness of the cladding layer reaches 960 HV0.2 at most, the cladding layer has high corrosion resistance, and compared with a 27SiMn base material, the abrasion resistance of the cladding layer is 7.3 times that of the 27SiMn base material. And due to the special proportion of the alloy powder, the alloy powder does not need to be too fine, laser cladding can be carried out in a coaxial powder feeding mode under the condition that forced cooling is not needed, and the process is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of laser cladding, in particular to a Nb-induced ultrafine crystallized Fe-based high-wear-resistant laser cladding layer and a cladding process thereof. Background Art

[0002] When 27SiMn steel is used in hydraulic supports, it not only has to withstand impact wear, but also has to deal with corrosion damage. In order to extend the service life of the hydraulic support, the grain size of the Fe-based cladding layer can be refined by laser cladding.

[0003] Patent ZL202010690870.1 discloses a highly corrosion-resistant submicron-nanocrystalline Fe-based laser cladding layer and a preparation method thereof. The method is to mix a certain proportion of alloy powder, and then pre-place the alloy powder on the surface of the substrate using water glass as a binder, and clad the pre-placed layer to obtain an ultrafine-grained Fe-based laser cladding layer. This method has high requirements on the powder particle size, and gradient particle size alloy powders need to be used, that is, the particle size range of reduced iron powder is 60μm-160μm, the particle size range of ferrovanadium powder is 20μm-40μm, and the particle size range of graphite powder is 8μm-12μm. If the synchronous powder feeding method is used, it is not easy to achieve, and the powder feeding head is easy to clog when the alloy powder particle size is too fine. Patent ZL 2023109602157 discloses a self-passivating highly corrosion-resistant Fe-VC composite laser cladding layer and a preparation method thereof. The method obtains a highly corrosion-resistant ultrafine-grained Fe-based laser cladding layer by forced cooling of the substrate. The cooling rate of obtaining a high corrosion-resistant cladding layer by forced cooling of the substrate is not easy to control and the process is complicated. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a Nb-induced ultrafine crystallized Fe-based high wear-resistant laser cladding layer and a cladding process thereof.

[0005] In order to solve the above technical problems, the present invention discloses a cladding process for a Nb-induced ultrafine crystallized Fe-based high wear-resistant laser cladding layer. A cladding layer is prepared on a 27SiMn steel substrate by a laser cladding method. The alloy powder used for cladding is composed of: 60.6wt.% reduced iron powder, 32.4wt.% ferrovanadium powder, 6.1wt.% graphite powder and 0.9wt.% niobium powder.

[0006] Preferably, the ferrovanadium powder is FeV50 with a vanadium content of 48% by mass, the reduced iron powder is spherical reduced iron powder, the particle sizes of the ferrovanadium powder, graphite powder and spherical reduced iron powder are all in the range of 100-200 mesh, and the particle size of the niobium powder is 400-600 mesh.

[0007] Preferably, synchronous powder feeding is used for cladding.

[0008] Preferably, the parameters of the laser cladding are: laser power 1000 W, cladding head 24 mm from the substrate surface, overlap rate 35%, pulse frequency 4500 Hz, duty cycle 95%, cladding speed 12 mm / s, pure argon with a flow rate of 6 L / min as powder feeding gas, and pure argon with a flow rate of 16 L / min as shielding gas.

[0009] The Nb-induced ultrafine crystallized Fe-based high wear-resistant laser cladding layer of the present invention is prepared by adopting any one of the above-mentioned cladding processes.

[0010] The beneficial effects of the present invention are as follows: the appropriate amount of Nb element in the present invention promotes the reduction of equiaxed grain size and the shortening of dendrite size. While the grain size is reduced, the grain boundary density increases, and the grain boundary is often more susceptible to corrosion, but it is conducive to the rapid formation of corrosion products, effectively preventing the corrosion medium from penetrating into the matrix. The average grain size of the cladding layer of the present invention reaches the submicron ultrafine grain scale of 0.96μm, and the average microhardness of the cladding layer reaches up to 960HV 0.2 The cladding layer has high corrosion resistance, and its abrasion resistance is 7.3 times that of the 27SiMn substrate. And due to the special ratio of the alloy powder, the alloy powder does not need to be too fine, and the coaxial powder feeding method can be used for laser cladding without forced cooling, which is a simple process. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 The optical microscopic morphology of the cladding layer a obtained in Example 1 of the present invention;

[0012] Figure 2 The optical microscopic morphology of the cladding layer b obtained in Comparative Example 1 of the present invention;

[0013] Figure 3 The optical microscopic morphology of the cladding layer c obtained in comparative example 2 of the present invention;

[0014] Figure 4 The optical microscopic morphology of the cladding layer d obtained in Comparative Example 3 of the present invention;

[0015] Figure 5 The optical microscopic morphology of the cladding layer e obtained in Comparative Example 4 of the present invention;

[0016] Figure 6 The secondary electron morphology of the cladding layer a obtained in Example 1 of the present invention;

[0017] Figure 7 The secondary electron morphology of the cladding layer b obtained in comparative example 1 of the present invention;

[0018] Figure 8 The secondary electron morphology of the cladding layer c obtained in comparative example 2 of the present invention;

[0019] Fig. 9 The secondary electron morphology of the cladding layer d obtained in comparative example 3 of the present invention;

[0020] Fig.10 The secondary electron morphology of the cladding layer e obtained in Comparative Example 4 of the present invention;

[0021] Fig.11 The average grain size diagram of cladding layers a, b, c, d, and e;

[0022] Fig.12 is the average microhardness of cladding layers a, b, c, d, and e;

[0023] Fig.13 Potentiodynamic polarization curves of cladding layers a, b, c, d, and e measured in 3.5 wt.% NaCl solution.

[0024] Fig.14 The wear volume of the cladding layer a and the 27SiMn steel substrate after the set load is 30N, the reciprocating frequency is 3Hz, the advance is 6mm, the material of the friction ball is Si3N4, and the friction time is 30min.

[0025] Fig.15 For the cladding layer a and the 27SiMn steel substrate, in 3.5wt.% NaCl solution, the load force is 15N, the rotation speed is 200r / min, the friction pair is an alumina ceramic ball, and the experimental time of corrosion wear is the wear volume after 2h. DETAILED DESCRIPTION

[0026] The specific embodiments and control examples are all prepared by the following method:

[0027] The cladding layer was prepared by laser cladding on the 27SiMn steel substrate in a synchronous powder feeding manner. The laser power was 1000 W, the laser gun head (i.e., cladding head) was 24 mm away from the substrate surface, the overlap rate was 35%, the pulse frequency was 4500 Hz, the duty cycle was 95%, the cladding speed was 12 mm / s, and pure argon with a flow rate of 6 L / min was used as the powder feeding gas, and pure argon with a flow rate of 16 L / min was used as the shielding gas.

[0028] Embodiment 1:

[0029] The alloy powder composition is 60.6wt.% reduced iron powder, 32.4wt.% ferrovanadium powder, 6.1wt.% graphite powder, and 0.9wt.% niobium powder, wherein the ferrovanadium powder adopts FeV50, the mass content of vanadium in the ferrovanadium powder is 48%, the reduced iron powder is spherical reduced iron powder, the particle size range of the ferrovanadium powder, graphite powder and reduced iron powder is 100-200 mesh, the particle size of the niobium powder is 400-600 mesh, and the cladding layer a is obtained.

[0030] Comparative Example 1:

[0031] The alloy powder composition is 61.5wt.% reduced iron powder, 32.4wt.% ferrovanadium powder, 6.1wt.% graphite powder, and 0wt.% niobium powder, wherein the ferrovanadium powder adopts FeV50, the mass content of vanadium in the ferrovanadium powder is 48%, the reduced iron powder is spherical reduced iron powder, the particle size range of the ferrovanadium powder, graphite powder and reduced iron powder is 100-200 mesh, the particle size of the niobium powder is 400-600 mesh, and the cladding layer b is obtained.

[0032] Comparative Example 2:

[0033] The alloy powder composition is 61.2wt.% reduced iron powder, 32.4wt.% ferrovanadium powder, 6.1wt.% graphite powder, and 0.3wt.% niobium powder, wherein the ferrovanadium powder adopts FeV50, the mass content of vanadium in the ferrovanadium powder is 48%, the reduced iron powder is spherical reduced iron powder, the particle size range of the ferrovanadium powder, graphite powder and reduced iron powder is 100-200 mesh, the particle size of the niobium powder is 400-600 mesh, and the cladding layer c is obtained.

[0034] Comparative Example 3:

[0035] The alloy powder composition is 60.9wt.% reduced iron powder, 32.4wt.% ferrovanadium powder, 6.1wt.% graphite powder, 0.6wt.% niobium powder, wherein the ferrovanadium powder is FeV50, the vanadium mass content of the ferrovanadium powder is 48%, the reduced iron powder is spherical reduced iron powder, the particle size range of the ferrovanadium powder, graphite powder and reduced iron powder is 100-200 mesh, the particle size of the niobium powder is 400-600 mesh, and the cladding layer d is obtained.

[0036] Comparative Example 4:

[0037] The alloy powder composition is 60.3wt.% reduced iron powder, 32.4wt.% ferrovanadium powder, 6.1wt.% graphite powder, and 1.2wt.% niobium powder, wherein the ferrovanadium powder is FeV50, the mass content of vanadium in the ferrovanadium powder is 48%, the reduced iron powder is spherical reduced iron powder, the particle size range of the ferrovanadium powder, graphite powder and reduced iron powder is 100-200 mesh, the particle size of the niobium powder is 400-600 mesh, and the cladding layer e is obtained.

[0038] See also Figure 1-5 , Optical microscopic morphologies of the cladding layers a, b, c, d, and e. The average grain sizes of the cladding layers a, b, c, d, and e are 0.96μm, 1.47μm, 1.28μm, 1.02μm, and 1.19μm, respectively.

[0039] See also Figure 6-10, The secondary electron morphology of the cladding layers a, b, c, d, and e shows that the carbides are aggregated and distributed along the grain boundaries. The average grain sizes of the carbides in the cladding layers a, b, c, d, and e are 0.29μm, 0.35μm, 0.31μm, 0.29μm, and 0.34μm, respectively.

[0040] See also Fig.11 , Average grain size diagram of cladding layers a, b, c, d, and e.

[0041] See also Fig.12 The average microhardness of the cladding layers a, b, c, d, and e is 960 HV respectively. 0.2 、770HV 0.2 、815HV 0.2 、955HV 0.2 and 865HV 0.2 When 0.9wt.% is added to Fe-based powder, the microhardness of the cladding layer is the highest, and the microhardness of cladding layer a is increased by 190HV relative to the microhardness of cladding layer b. 0.2 , about 6.40 times that of 27SiMn steel.

[0042] See also Fig.13 , the potentiodynamic polarization curves of cladding layers a, b, c, d, and e measured in 3.5wt.% NaCl solution, and the fitting results of the polarization curves are shown in Table 1. It can be seen that the self-corrosion current density of cladding layer b is 22.7 times that of cladding layer a, cladding layer a has the best corrosion resistance, and micro-passivation occurs in the polarization curve of cladding layer a.

[0043] Table 1 Polarization curve fitting results

[0044]

[0045] See also Fig.14 The wear volume of the cladding layer a is 1.15×10 after the set load is 30N, the reciprocating frequency is 3Hz, the advance is 6mm, the material of the friction ball is Si3N4, and the friction time is 30min. 7 μm 3 Under the same conditions, the wear volume of 27SiMn steel substrate is 1.57×10 8 μm 3 The anti-friction and wear performance of the cladding layer a is 13.6 times that of the 27SiMn steel substrate.

[0046] See also Fig.15 The wear volume of the cladding layer a in 3.5wt.% NaCl solution is 1.115×107 μm 3 Under the same conditions, the wear volume of 27SiMn steel substrate is 1.535×10 6 μm 3 The wear resistance of the cladding layer a is 7.3 times that of the 27SiMn steel substrate.

[0047] It can be concluded from the above embodiments and control examples that an appropriate amount of Nb element promotes the reduction of equiaxed grain size and the shortening of dendrite size. While the grain size is reduced, the grain boundary density increases, and the grain boundaries are often more susceptible to corrosion, but it is conducive to the rapid formation of corrosion products, effectively preventing the corrosive medium from penetrating into the interior of the matrix. The microstructure of the cladding layer is composed of dendrites and equiaxed grains. After adding the Nb element, the dendrites transform into equiaxed crystals, and the cladding layer is composed of equiaxed grains with fine grains. When the Nb addition amount is 0.9wt.%, the in-situ autogenous carbides increase at the grain boundaries, hindering the growth of grains. Therefore, the average grain size is the smallest, and the average grain size of the cladding layer reaches the submicron ultrafine grain scale of 0.96μm. When the Nb addition amount is 0.9wt.%, the average microhardness of the cladding layer reaches a maximum of 960HV 0.2 When the addition amount of Nb is 1.2wt.%, due to the coarsening of carbides and agglomeration at the grain boundaries, as well as the latent heat of phase transformation, the grain size increases, the fine grain strengthening effect weakens, and the hardness decreases. When carbides aggregate and coarsen, galvanic corrosion will be aggravated, resulting in an increase in the cathode area of ​​a single corrosion unit, further enhancing galvanic corrosion. The cladding layer with a Nb content of 0.9wt.% has a suitable carbide particle size and a minimum average grain size, so the corrosion resistance of this cladding layer is the best.

[0048] During abrasion, along with electrochemical corrosion, Cl- continuously acts on the grain boundaries, the matrix undergoes redox reaction, large-area pitting occurs, and the surface roughness of the matrix increases. During the friction process, the corrosion products of the matrix fall off and many holes appear. Cl- penetrates into the matrix along the holes, the corrosion of the substrate gradually deepens, the anode dissolves, and metal ions are precipitated. During the friction process between the friction pair and the substrate, the detached corrosion products are constantly taken away, and the adhesive wear phenomenon becomes more and more serious. The peeled debris particles continue to undergo abrasive wear with the substrate under the movement of the friction pair, forming a vicious cycle, and deep and wide grooves appear. The grain size of the cladding layer a is small, and the grain boundary density increases. During the electrochemical corrosion process, the grain boundary is corroded first, and oxides such as Nb2O5 are produced and attached to the grain boundary, blocking the corrosion channel in the cladding layer, reducing the corrosion depth of the cladding layer, and improving the corrosion resistance of the cladding layer. The anti-wear performance of the cladding layer a is 7.3 times that of the 27SiMn substrate.

[0049] The above descriptions are only preferred embodiments of the present invention and are not intended to limit the present invention. Those skilled in the art will appreciate that various changes, modifications, substitutions and variations may be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A cladding process for a Nb-induced ultrafine crystallized Fe-based high wear-resistant laser cladding layer, characterized in that: A cladding layer was prepared on a 27SiMn steel substrate by laser cladding. The alloy powder used for cladding consisted of 60.6wt.% reduced iron powder, 32.4wt.% ferrovanadium powder, 6.1wt.% graphite powder and 0.9wt.% niobium powder.

2. The cladding process of the Nb-induced ultrafine crystallized Fe-based high wear-resistant laser cladding layer according to claim 1 is characterized in that: The ferrovanadium powder is FeV50 with a vanadium content of 48% by mass, the reduced iron powder is spherical reduced iron powder, the particle sizes of the ferrovanadium powder, graphite powder and spherical reduced iron powder are all in the range of 100-200 meshes, and the particle size of the niobium powder is 400-600 meshes.

3. The cladding process of the Nb-induced ultrafine crystallized Fe-based high wear-resistant laser cladding layer according to claim 2 is characterized in that: The cladding is carried out by synchronous powder feeding.

4. The cladding process of the Nb-induced ultrafine crystallized Fe-based high wear-resistant laser cladding layer according to claim 3 is characterized in that: The parameters of the laser cladding are: laser power 1000 W, cladding head 24 mm from the substrate surface, overlap rate 35%, pulse frequency 4500 Hz, duty cycle 95%, cladding speed 12 mm / s, pure argon with a flow rate of 6 L / min as powder feeding gas, and pure argon with a flow rate of 16 L / min as shielding gas.

5. A Nb-induced ultrafine crystallized Fe-based high wear-resistant laser cladding layer, characterized in that: The method is prepared by using a cladding process as described in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Iron-based composite material and preparation method thereof

    CN102134677A

  • High-corrosion-resistance submicron-nanocrystalline Fe-based laser cladding layer and preparation method thereof

    CN111809178A

  • Pulse plasma arc cladding layer and cladding process thereof

    CN116356313A

  • Submicron-nano Fe-based plasma cladding layer and preparation method thereof

    CN116695116A

Cited By

  • Cu-induced passivation Fe-based high-corrosion-resistance laser cladding layer and cladding process thereof

    CN120366767A

  • Iron-based wear-resistant corrosion-resistant coating for marine environment and preparation method of iron-based wear-resistant corrosion-resistant coating

    CN121065692A